Behavioral coping strategies predict tumor development and behavioral impairment after chronic social stress in mice - Goñi-Balentziaga, Olatz; Garmendia, Larraitz; Labaka, Ainitze; Lebeña, Andrea; Beitia, Garikoitz; Gómez-Lázaro, Eneritz; Vegas, Oscar (Physiology & behavior, 2020)
•Chronic social defeat reduce sucrose consumption.•Three types of behavioral strategies to cope with social stress were revealed.•Passive mice show the highest tumor development and depressive-like behavior.•Active strategy, but not aggressive behavior, protects mice from tumor development.•Active/NonAggressive mice show the highest HPA activation after the 1st interaction. The aims of this study were to identify behavioral strategies to cope with social defeat, evaluate their impact on tumor development and analyze the contributions of both to changes in physiology and behavior produced by chronic defeat stress. For this purpose, OF1 mice were inoculated with B16F10 melanoma cells and subjected to 18 days of repeated defeat stress in the presence of a resident selected for consistent levels of aggression. Combined cluster and discriminant analyses of behavior that manifested during the first social interaction identified three types of behavioral profiles: active/aggressive (AA), passive/reactive (PR) and an intermediate active/non-aggressive (ANA) profile. Animals that showed a PR coping strategy developed more pulmonary metastases at the end of the social stress period than animals in other groups. The ANA but not AA group also showed higher tumor metastases than non-stressed subjects. In addition, the ANA group differed from the other groups because it displayed the highest corticosterone levels after the first interaction. Chronic stress reduced sucrose consumption, which indicates anhedonia, in all the stressed groups. However, the PR subjects exhibited a longer immobility time and swam for less time than other subjects in the forced swim test (FST), and they travelled a shorter distance in the open field test (OFT). In this test, the ANA group also travelled smaller distances than the non-stressed group, but the difference was more moderate. In contrast, tumor development but not stress increased behaviors associated with anxiety in the OFT (e.g., time in the center) in all tumor-bearing subjects. In summary, although the effects of social stress and tumor development on behavior were rather moderate, the results indicate the importance of behavioral coping strategies in modulating the effects of chronic stress on health.